Case Studies Of Pilot Projects ( Series I) For The Utilization Of Rural Manpower - Planning Commission (Planning Commission, 1962)
"It was on 14th October, 1960, that the Planning Commission informed, the State Governments about the approach envisaged, in the Third. Plan to works programmes for the utilization of rural manpower. The objective and. content of the programme were outlined in this communication, along with the decision to initiate it with about 2? pilot projects each costing roughly Rs. 2 lakhs. The State Governments were invited to submit proposals for these projects by 15th November, i960, so that the Projects could get started not later than the beginning of 1961 and the allocation for the first series utilized before the end of the financial year 1961-62."
Planning Commission Government Of India